Quantum Dots: Ultrafast Solar‐Blind Ultraviolet Detection by Inorganic Perovskite CsPbX3 Quantum Dots Radial Junction Architecture (Adv. Mater. 23/2017). Issue 23 (June 2017) - Lu, Jiawen; Sheng, Xuexi; Tong, Guoqing; Yu, Zhongwei; Sun, Xiaolin; Yu, Linwei; Xu, Xiangxin; Wang, Junzhuan; Xu, Jun; Shi, Yi; Chen, Kunji
Abstract : Ultrafast solar‐blind UV detection, enabled by a hybrid inorganic perovskite CsPbX3 quantum‐dot radial junction architecture, achieves rise/fall response times of 0.48/1.03 ms and a high responsivity of 54 mA W −1 at 200 nm without an external power supply, as described by Linwei Yu, Xiangxing Xu, and co‐workers in article number1700400 . These results pave the way toward large‐area manufacturing of high‐performance Sibased perovskite UV detectors in a low‐cost procedure.